What is the influence of cinnamon supplementation on liver enzymes? A systematic review and meta‐analysis of randomized controlled trials. (1st July 2021) - Mousavi, Seyed Mohammad; Jayedi, Ahmad; Bagheri, Amir; Zargarzadeh, Nikan; Wong, Alexei; Persad, Emma; Akhgarjand, Camellia; Koohdani, Fariba
Abstract : Existing evidence has uncovered the potential health benefits of cinnamon intake; however, its effect on liver function is unclear. Thus, the aim of this systematic review and meta‐analysis was to examine the effect of cinnamon supplementation on liver enzymes. Relevant articles were identified through a systematic search in PubMed/Medline, Scopus, Web of Science, Cochrane Library, and Embase up to September 2020. All trials assessing the effect of oral cinnamon supplementation on serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) in adults were included. The pooled effect sizes were obtained using the random‐effects model and expressed as mean difference (MD) and 95% confidence intervals (CI). A total of seven original trials (nine treatment arms) involving a total of 256 subjects were included in the final analysis. The pooled analysis indicated that cinnamon supplementation had no significant effect on serum levels of ALT, AST, and ALP. However, there was a significant reduction in ALT levels in patients with type 2 diabetes (MD: −4.01 U/L; 95% CI: −6.86, −1.15) and in trials with low‐dose supplementation (<1, 500 mg/d), follow‐up duration longer than 12 weeks, and in the elderly patients (aged>50 years). The beneficial effects of cinnamon intake were also shown in AST levels in patients with type 2 diabetes and trials with long‐term follow‐up (>12 weeks). Longer‐term, oral cinnamon supplementation may improve serum levels of liver enzymes in patients with type 2 diabetes. Further high‐quality studies are needed, especially in populations with abnormal liver enzyme levels, to firmly establish the clinical efficacy of cinnamon on liver function.